Creating smiles the lip repositioning way a case report - Nikhila Chandramohan, Dr.; Lalith Vivekanand, Dr.; Swetha A, Dr.; Faiza Fathima, Dr. (International Journal of Dental Research, 2022)
A beautiful smile comprises a perfect balance of the white and pink. A gummy smile has been a prevalent esthetic disorder with varied etiologies including of skeletal, dento-alveolar, or soft-tissue origin. It can be managed by a variety of treatment modalities after appropriate diagnosis and treatment planning. If it is due to jaw deformities, altered passive eruption or tooth malpositioning, the corrective measures incorporate orthognathic surgery and orthodontic treatment. However, this requires hospitalization and entails significant discomfort. Lip repositioning is a simple and predictable technique that restricts the muscle pull of the elevator lip muscles thereby reducing the gingival display. This case report demonstrates the successful management of a young patient with moderate gummy smile using the conventional LR surgery thereby proving to be a promising alternative that is less invasive in nature and with minimal postop complications. At 6 months, the results were stable.Â Â Â